METHODS USED IN THE FIELD OF DISINFECTION OF AGRICULTURAL PRODUCTS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article provides information on physical, chemical, and heat treatment methods used in the field of disinfection of quarantined products, as well as international experience.